Enhancement of antibody class switch recombination by the cumulative activity of four separate elements() - Dunnick, Wesley A. (2011)
Class switch recombination of antibody isotype is mediated by a recombinational DNA deletion event, and must be robustly upregulated during antigen-driven differentiation of B cells. The enhancer region 3′ of the Cα gene is important for the upregulation of switch recombination. Using a transgene of the entire heavy chain constant region locus, we now demonstrate that it is the four 3′ enhancer elements themselves (a total of 4.7 kb) that are responsible for the upregulation, rather than the 24 kb of DNA in between them. Neither allelic exclusion nor transgenic μ expression is reduced by deletion of the four 3′ enhancers. We also test deletions of two or three of the 3′ enhancers, and show that deletion of more 3′ enhancers results in a progressive reduction in both switch recombination and germline transcription of all heavy chain genes. Nevertheless, we find evidence for special roles for some 3′ enhancers--different heavy chain genes are affected by different 3′ enhancer deletions. Thus, we find that the dramatic induction of class switch recombination during antigen-driven differentiation is the result of an interaction among four separated regulatory elements.